2018
DOI: 10.1093/scan/nsy065
|View full text |Cite
|
Sign up to set email alerts
|

Thinking of attachment figures blocks differential fear conditioning

Abstract: Thinking of attachment figures can potentially impact acquisition and extinction of fear memories. In this study, 50 participants underwent a fear conditioning and extinction paradigm. Half the participants thought about a supportive attachment figure and half thought about a non-attachment positive experience prior to the fear conditioning. All participants then underwent a differential fear conditioning and fear extinction paradigm, and returned 2 days later for an extinction recall task. Fear-potentiated st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 26 publications
3
25
1
1
Order By: Relevance
“…Attachment style modulated theta power when accompanied by one’s partner. Other studies show that just the mere imagined presence of a secure attachment figure attenuates fear learning (Toumbelekis et al ., 2018), underscoring the emotional impact of partner presence. This was interpreted to reflect evolutionary shaped learning (Hornstein & Eisenberger, 2018; Seligman, 1970).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attachment style modulated theta power when accompanied by one’s partner. Other studies show that just the mere imagined presence of a secure attachment figure attenuates fear learning (Toumbelekis et al ., 2018), underscoring the emotional impact of partner presence. This was interpreted to reflect evolutionary shaped learning (Hornstein & Eisenberger, 2018; Seligman, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiously as compared to securely attached individuals show elevated psychophysiological responses to stressful stimulation in presence of their partner, when compared to unknown participants, whereas securely attached individuals do not (e.g., Carpenter & Kirkpatrick, 1996). Further, the imagined presence of a secure attachment figure attenuates fear learning, supporting an impact on basic learning processes (Toumbelekis, Liddell & Bryant, 2018), underscoring the emotional power of partner presence. Thus, we forward the hypothesis that relatively secure partner attachment will attenuate EEG power more than insecure attachment.…”
Section: Introductionmentioning
confidence: 90%
“…For example, in adult rats, the presence of a cage mate significantly attenuates fear learning, compared to those conditioned alone and engages the vmPFC (Kiyokawa et al, 2014, 2007; Penha Farias et al, 2019). This effect also occurs in humans and involves the vmPFC; in adults, the presence of an important social partner (i.e., mother, romantic partner, cage mate) or a stimulus that provokes the memory of an individual (i.e., odor, photo) dampens fear through amygdala-vmPFC to block adult fear learning across species (Guzmán et al, 2009; Fuzzo et al, 2015; Hornstein et al, 2016; Hornstein and Eisenberger, 2017; van Rooij et al, 2017; Toumbelekis et al, 2018). Our results also overlap with the literature involving non-social cues predicting safety within a threatening situation: conditioned inhibitors/safety signals use a similar network of PFC input suppressing the amygdala (Rogan et al, 2005; Pollak et al, 2008; Christianson et al, 2012; Harrison et al, 2017; Levin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the required sample size on the basis of a prior study of fear acquisition following attachment priming [ 10 ]. Using the parameters of this prior study, the power analysis indicated that to identify an effect of attachment priming on subsequent fear recall, we would require at least 42 participants in each condition (90% power, α = 0.05, two-tailed).…”
Section: Methodsmentioning
confidence: 99%